Adsorption mechanism of propyl gallate as a flotation collector on scheelite: A combined experimental and computational study. (15th March 2019) - Lyu, Fei; Sun, Wei; Khoso, Sultan Ahmed; Zhang, Chenyang; Liu, Runqing; Wang, Li; Gao, Jiande
Graphical abstract: Highlights: PG is a promising collector for scheelite due to no metal ion activation needed. PG chelates with Ca sites in the scheelite surfaces forming five-member rings. Activate phenolic hydroxyl groups offer new insights for collector development. Abstract: In this study, propyl gallate (propyl 3, 4, 5-trihydroxybenzoate; PG) was introduced as a collector for scheelite. The adsorption mechanism on the scheelite surface was investigated by computational and experimental methods, including first principle calculations and Fourier transform infrared (FTIR) spectroscopy. Flotation experiments were conducted to investigate the flotation performance of PG on scheelite. Ethyl p-hydroxybenzoate (EPHB) and ethyl 3, 4-dihydroxybenzoate (EDHB), acting separately as collectors for scheelite, were also investigated for comparison. Our results consistently demonstrated that PG chemisorbed onto the scheelite surface by forming a five-member ring through its ortho oxygens. As speculation, the chelating ability of PG was greater than that of EDHB, and EPHB cannot coordinate to Ca(II), which was in excellent agreement with FTIR results. The flotation results showed that PG exhibited an excellent collecting ability for scheelite, followed by the weaker collecting ability of EDHB. EPHB had nearly no ability to collect scheelite, thus confirming the first principle calculation and FTIR analysis. In addition, PG has a stronger ability to collect scheelite than BHA without activation by any metallic ions. Overall, PG is a promising scheelite collector for application and the activate polyphenolic hydroxyl groups offer a new insight for the development of flotation collectors.